Education- and income-based inequalities of functional dentition by dental service utilization - Anna Rachel dos Santos Soares; Carlos Antonio Gomes da Cruz; Maria Luíza Viana Fonseca; Líria Sheila Chamane; Loliza Luiz Figueiredo Houri Chalub; Raquel Conceição Ferreira (Frontiers in Oral Health)
IntroductionThis study analyzed the magnitude of education- and income-based inequalities in functional dentition (FD) among Brazilian adults between 2013 and 2019, considering dental service utilization.MethodsThis study based on repeated cross-sectional surveys using secondary data from a probabilistic sample of adults (18–59 years old) who participated in the 2013 and 2019 National Health Survey (NHS). Only individuals who reported having used dental services were included. FD was defined as having ≥21 teeth, based on self-reported tooth loss in the maxillary and mandibular arches. Variables included sex, age, education (years of study), and per capita family income (measured in minimum wages). Dental service utilization was assessed using the question “When was the last time you visited a dentist?” with responses dichotomized into “>1 year” and “≤1 year”. Absolute and relative inequalities in FD were assessed using the slope index of inequality (SII) and the relative index of inequality (RII), respectively, based on education and income. Generalized linear models (log-binomial regression) were applied with a logarithmic link function to estimate RII (rate ratios) and an identity link function to estimate SII (rate differences), adjusting for sex and age. Trends between 2013 and 2019 and differences in SII and RII by dental service utilization were assessed through two-way interaction terms in the models. All analyses accounted for the survey's complex sampling design and sample weights.ResultsThe prevalence of FD was 85.95% (2013) and 89.45% (2019) (p < 0.001). SII and RII indicated greater FD prevalence among higher socioeconomic groups, with the magnitude of education-based inequality higher than income-based inequality. Education-based inequalities decreased from 2013–2019. Educational inequalities were more pronounced among those who used dental services >1 year (p < 0.001), whereas income-based inequalities did not differ by dental service utilization (p > 0.05).ConclusionsDespite the reduction in FD education-based inequality in Brazil, persistent disparities were observed between socioeconomic groups, with the lowest inequalities found among adults who used dental services ≤1 year. This indicates the importance of interventions aimed at reducing barriers and promoting access to services for the most vulnerable populations.